2021
DOI: 10.1371/journal.pone.0256495
|View full text |Cite
|
Sign up to set email alerts
|

Intentional and unintentional non-adherence to social distancing measures during COVID-19: A mixed-methods analysis

Abstract: Social distancing measures implemented by governments worldwide during the COVID-19 pandemic have proven an effective intervention to control the transmission of SARS-CoV-2. There is a growing literature on predictors of adherence behaviours to social distancing measures, however, there are no comprehensive insights into the nature and types of non-adherence behaviours. To address this gap in the literature, we studied non-adherence in terms of counts of infringements and people’s accounts on their behaviours … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…More studies than not found that trust in public institutions was associated with behaviour/intentions. People with higher trust in science [ 27 ], confidence in government [ 21 , 25 , 28 ] and confidence in the health system [ 25 ] were more adherent than people who had lower trust in the TRBs self-isolating, leaving the house, physical distancing and hand hygiene. However, in two studies from the same project [ 22 , 24 ], trust in government was not associated with self-isolating and leaving the house behaviours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More studies than not found that trust in public institutions was associated with behaviour/intentions. People with higher trust in science [ 27 ], confidence in government [ 21 , 25 , 28 ] and confidence in the health system [ 25 ] were more adherent than people who had lower trust in the TRBs self-isolating, leaving the house, physical distancing and hand hygiene. However, in two studies from the same project [ 22 , 24 ], trust in government was not associated with self-isolating and leaving the house behaviours.…”
Section: Resultsmentioning
confidence: 99%
“…Intention was associated with physical distancing [18][19][20], hand hygiene [18][19][20], face covering [18,20] and leaving the house (e.g. only leaving the house for permitted reasons such as essential shopping) [19][20][21][22]. There was no clear pattern of association between any of the other TDF theoretical domains and adherence to TRBs/intentions.…”
Section: Psychological Associations With Behaviourmentioning
confidence: 92%
“…Basile et al took Reddit as their research object, considered structural variations in social posting behavior and emotional reactions based on the Plutchik model of basic emotions and unconventional emotions, and also studied the specific reactions of social posting during the pandemic versus normal periods [ 10 ]. Eraso et al studied intentional and unintentional non-adherence to social distancing measures during COVID-19 and put forward suggestions for improvement [ 11 ].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…However, a minority of these countries' citizens have questioned the legitimacy of depending on the views of these non-elected officialswho base their advice on continually updated scientific studies-for devising COVID-19 policy [45]. Their response has been to undermine officially endorsed protective measures against the virus, both unintentionally and intentionally [46]. This includes refusing to wear masks [47] or receive vaccines [48], often concurrently; however, not necessarily [49].…”
Section: Government Responses To Covid-19mentioning
confidence: 99%